Medical Laboratory Technologists as Positive Quality Improvement Team Members - Dennis Kendel (HealthcarePapers, 2017)
While Medical Laboratory Technologists (MLTs) do not generally work directly with clinical healthcare teams they have proven to be invaluable contributors to team-based systematic quality improvement in healthcare. They were early adopters of standardized systemic performance measures coupled with explicit strategies for improving suboptimal performance. Their attentiveness to systemic analysis of systemic factors influencing performance has proven to be valuable in our quest to make care optimally safe and high quality.
Keywords: Professional regulation, evolving practice, scope of practice, professional oversight, health human resources